Mask vs. tent: effect of hypoxia method on repeated sprint ability and physiological parameters in cyclists - Vasquez-Bonilla, A. A.; Rojas-Valverde, D.; Feliu-Ilvonen, J. M.; Timón, R.; Olcina, G. (Sport Sciences for Health, 2024)
This study aimed to evaluate the effect of repeated sprint in hypoxia (RSH) training in mask vs. tent system on the physiological parameters associated with the cyclist`s performance. Sixteen well-trained cyclists (VO2max 66 ± 5.9 mL/kg/min) participated in a randomised and two parallel groups design. Participants were assigned to different hypoxia methods [RSHMask (n = 8) vs RSHTent (n = 8)]. The sprint number and power output were measured during a repeated sprint test to failure before and after the effect of eight sessions of RSH. In addition, the following physiological parameters were evaluated: oxygen consumption (VO2), heart rate (HR), arterial oxygen saturation (SpO2), muscle oxygen saturation (SmO2), lactate and core temperature (CoreT°). Linear mixed models were used for repeated measures (p value < 0.05), and the effect size (ES) between groups was reported. An inter-individual analysis of participants was also reported. There was an increase in sprint numbers in both groups (ES = 0.167, p = 0.023) and an increase in power output (?w) in the RSHMask group (ES = 0.095, p = 0.038). The RSHMask group showed improvement in VO2 recovery (ES = 0.096, p = 0.031) and SmO2 desaturation % (ES = 0.112, p = 0.042) compared to the RSHTent group. Likewise, 50% of the participants in RSHTent showed adaptations to withstand higher T°Core (+ 0.45°), and eight participants showed lactate decreases between 2.9 and 3.1 mmol/L (-24%) after RSH in both groups. Generally, RSH improves the cyclist`s performance, whether the mask or tent method is used. However, RSHTent has the advantage of causing adaptations in T°Core, whilst RSHMask improves anaerobic performance in the oxygenation of peripheral muscles.